Effects of waste glass powder as pozzolanic material in saw dust cement brick (2014)
This work examines the possibility of using Waste Glass Powder (WGP) as a partial replacement of cement in saw dust composite brick to assess its pozzolanic activity and its effect on the properties of the composite. WGP was used to partially replace cement at 0%, 5%, 10%, 15%, 20%, 25%, and 30% in the production of test samples of 100x100x100mm at binder sand mixing ratio of 1:6. After casting the cubes, they were tested for compressive strength, water absorption, capillary water absorption and volume porosity. The results indicated that WGP can be used as cement replacement material up to 30% at particle size less than 100μm to prevent alkali silica reaction and this can be utilized in the manufacture of non-load bearing sandcrete block without any unfavourable effect. The study further revealed that waste glass, if ground finer than 100μm shows a pozzolanic behaviour because it reacts with lime at early stage of hydration forming extra CSH gel thereby forming denser cement matrix. The early consumption of alkalis by glass particles mitigate alkali-silica reaction by increasing durability of composite brick which is manifested in the result of volume porosity, water absorption, capillary absorption as well as in the results of sample densities.